First Theoretical Evidence of Blue-Shifted Energy Transfer in Bioluminescence (Communications in Computational Chemistry, 2025)
Energy transfer (ET) complex is not rare inbioluminescence. Usually, the ET occurs from the donor withhigher emission energy to the acceptor with lower absorptionenergy. However, a blue-shifted ET is observed in thebioluminescence (BL) of Photobacterium phosphoreum (PP). Theluminophore, 4a-hydroxy-5-hydro-flavin mononucleotide at thefirst singlet excited state ($S_1$-HFOH), in solitary PP luciferase(PPLuc) emits light at 495 nm. When a proportional concentrationof lumazine protein (LumP) with a substrate of 6,7-dimethyl-8-ribityllumazine (DLZ) is introduced, the emission wavelength changes to 475 nm, accompanied by a 2.1-fold enhancementin intensity. The blueshift is only an observation, whose ET mechanism has not been uncovered over fifty years of research.In the present article, we evidenced that the ET process occurs via a Förster resonance energy transfer (FRET) mechanismby protein-protein docking and molecular dynamics (MD) simulations. Moreover, utilizing the combined quantummechanics and molecular mechanics (QM/MM) method, we calculated the FRET rate and fluorescence quantum yield. Thesmall Stokes shift of DLZ as well as the strong vibronic couplings of HFOH allow the blue-shifted FRET process. Thecalculated FRET rate is larger than the radiative and non-radiative decay ones of $S_1$-HFOH, and the fluorescence quantumyield of $S_1$-DLZ is higher than the one of $S_1$-HFOH, which clearly explains the experimentally observed enhancement ofthe emission intensity. Simultaneously, the blue-shifted FRET mechanism firstly interpreted that the wild-type PP emits475 nm BL rather than 490 nm one as the other species of bioluminescent bacteria do. This first-time deep investigationestablishes a theoretical research paradigm for the theoretical study of ET and holds significance in color regulation in theBL field.